High glass transition catalyst-free polybenzoxazine vitrimer through one-pot solventless method - Anagwu, Festus Ifeanyi; Dossi, Eleftheria; Skordos, Alexandros A. (Elsevier, 2025)
A high glass transition polybenzoxazine has been synthesised by a one-pot solventless method via the Mannich condensation of a phenolic disulphide, paraformaldehyde and aniline. The solventless process reduces synthesis time, material costs, and the need for post-synthesis purification. The polybenzoxazine exhibits a glass transition temperature (Tg) of 155 °C and thermosetting behaviour below this temperature. Dynamic disulphide bond metathesis associated with a topological freezing temperature of 78 °C and an activation energy of 127 kJ/mol delivers vitrimeric functionality with fast, catalyst-free stress relaxation above Tg. This material fully relaxes stress within 5 s at 190 °C, with thermal degradation beginning above 250 °C. It exhibits a glassy modulus of 3.6 GPa, high char yield (57.4 %) translating to a high limiting oxygen index (LOI) of 40.5 % and excellent environmental resistance, as evidenced by low water uptake (1.4 %) after immersion at 75 °C for 31 days. The combination of environmental resistance, due to thermosetting character, high glass transition, facile synthesis, high char yield, good processability, and fast stress relaxation position this polybenzoxazine as a promising candidate matrix system for repairable aerospace thermosetting continuous fibre composites.
Keywords: Polybenzoxazine; Vitrimer; Aerospace; Composites; 3403 Macromolecular and Materials Chemistry; 34 Chemical Sciences; Polymers; 4004 Chemical engineering